Safety of sunitinib in renal cell carcinoma. Issue 2 (12th March 2012) - Cañamares, I.; Agustin, M.J.; Santander, C.; Gomez-Tijero, N.; LLama, N. de la; Abad-Sazatornil, M.R.
Abstract : Background: Renal cell carcinoma (RCC) represents only 2-3% of all cancers. Sunitinib is a standard initial therapy in advanced and metastatic renal cell carcinoma. Purpose: A retrospective review was performed to assess the safety of sunitinib in RCC. Materials and methods: RCC patients undergoing sunitinib treatment and follow-up for at least one month were included. Variables: sex, age, nephrectomy status, histology, risk group, metastatic sites, sunitinib starting dose, % adverse events (AEs) from Common Terminology Criteria for Adverse Events (CTCAE version 4.0), % grade 3-4 AE, % starting dose reduction, % extra week rest period and % colony stimulating factors (CSF) used for toxicity management. Statistical analysis by SPSS 18.0. Results: 19 patients were analysed: 73.7% male, median age 62 years, 94.7% previously nephrectomised (78.9% radical nephrectomy and 15.8% partial nephrectomy), median time to sunitinib treatment 60.5 months. By histology, 79.0% was clear cell carcinomas. Grouped according to their risk (57.9% of patients could be assessed for risk): 15.8% were assessed as favourable, 26.3% intermediate and 15.8% unfavourable. Median metastatic sites were 3, sorted by frequency: lung 68.4%, liver 47.4%, soft tissues 26.3%, bone and pleura 21.1%, brain, skin and heart 10.5%. Starting dose of sunitinib were 68.4% 50 mg/day, 26.3% 37.5 mg/day and 5.3% 25 mg/day administered for four consecutive weeks and followed by a two-week rest period. 100% patients reported at least one AE. The most frequent AEs were asthenia 11.6%, neutropenia or thrombocytopenia 10.7%, hypertension or diarrhoea 9.9%. Grade 3-4 events were neutropenia 4.1%, anaemia 2.5%, bleeding 1.6%, hypertension, hand-foot syndrome or diarrhoea <1.0%. In addition, one case of toxic hepatitis and a cerebral oedema event were reported. Median cycles sunitinib received were 4.3. Toxicity management consisted of dose reduction 38.4%, extra week rest period 57.6%, no patients required CSF as filgrastim or epoetin α. Conclusions: With sunitinib, adverse events such as hematologic toxicity, asthenia, hypertension and gastrointestinal events were common. Toxicity management included dose reduction or additional rest period.